Analisis Rantai Pasok Budidaya Ikan Lele Pada UMKM Easy Farm Indonesia - Doni Sahat Tuan Manalu; Inayatul Maula; Nisrina Ayushafa Deanova; Putri Luciyani Gunawan; Tifany Claudia Siallagan; Adam De Al Varoziq; Nur Faizatul Lutfiah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Indonesia's significant potential in the fisheries sector, particularly in catfish aquaculture, offers substantial opportunities for economic development and business growth. This study analyzes the catfish supply chain from Easy Farm in Bekasi, West Java, to end consumers through middlemen and restaurants. Two supply streams are examined to evaluate efficiency, identify potential improvements, and provide strategic recommendations for supply chain management. Analytical methods include performance measurement, barrier identification, and evaluation of potential efficiency enhancements. Findings indicate that collaboration with middlemen and restaurants can expand market reach but also pose challenges related to supply quality and sustainability. Recommendations include investment in infrastructure and technology, increased collaboration with supply chain partners, and the development of sustainable marketing strategies.